Textbook on employment law - Honeyball, Simon (Oxford Univ. Press, 2008)
'Honeyball and Bowers' now includes more diagrams and flowcharts, and the discrimination and unfair dismissal sections have been thoroughly updated in light of recent legislation. This work remains a concise yet analytical introduction to employment law.
Keywords: Europäische Union; Labor laws and legislation -- Great Britain; Arbeitsrecht; Großbritannien; Einführung